Evaluation of hydrotherapy, using passive tests and power tests, for recovery across a cyclic week of competitive Rugby Union - Higgins, T. R.; Climstein, M.; Cameron, M. (The Journal of Strength and Conditioning Research, 2013)
In team sports, a cycle of training, competition, and recovery occurs weekly during the competitive season. In this research, we evaluated hydrotherapy for recovery from a simulated game of rugby union tracked over a week of training. Twenty-four experienced male rugby union players (mean ± SD age 19.46 ± 0.82 years, weight 82.38 ± 11.12 kg, height 178.54 ± 5.75 cm) were randomly divided into 3 groups: cold water immersion (n = 8), contrast bath therapy (n = 8), and a control group (n = 8). The 2 forms of hydrotherapy were administered immediately after a simulated rugby game. Testing was conducted 1 hour before the game and at 5 intervals postgame: 1, 48, 72, 96, and 144 hours. Dependent variables included countermovement jump, 10- and 40-m sprints, sessional rating of perceived exertion (RPE), flexibility, thigh circumference, and self-reported delayed onset muscle soreness (DOMS). Significant differences in DOMS were found between the cold water immersion and contrast bath groups at 48 hours post intervention (p = 0.02), and between the control and contrast bath groups at 72 (p = 0.03) and 96 (p = 0.04) hours post intervention. Cold water immersion and contrast bath groups reported significantly different RPE at 72 hours (p = ?) and 96 hours post (p = 0.05) intervention. Athletes' perceptions of muscle soreness and sessional RPE scores for training were greater in the contrast bath group (20%) after the simulated game and throughout the training week. Although results from passive and power tests were inconclusive in determining whether cold water immersion or passive recovery was more effective in attenuating fatigue, results indicated contrast baths had little benefit in enhancing recovery during a cyclic week of rugby union.